Risk-taking behavior in the U.S. thrift industry: Ownership structure and regulatory changes - Knopf, John D.; Teall, John L. (Journal of Banking & Finance, 1996)
We examine the relationship between U.S. thrift institution ownership structure and risk taking along with the impact of the Financial Institutions Reform, Recovery and Enforcement Act of 1989 (FIRREA) on this relationship. Our results, based on various indicators of risk, suggest that insider controlled thrifts were more likely to engage in risk taking prior to 1989 than were diversely held institutions. FIRREA seems to have curtailed much of this risk taking. We find inverse relationships between risk-taking and levels of institutional shareholdings. This along with other evidence suggests that the motive for risk-taking was not maximization of the ‘option’ value of shares as has been reported elsewhere. We also find evidence that entrenched managers may have generated significant private benefits.